The Arabic manuscript tradition : a glossary of technical terms and bibliography - Gacek, Adam (Brill, 2001)
Covering the entire spectrum of Arabic manuscripts, and especially the handwritten book, this book consists of a glossary of technical terms and a bibliography. The technical terms, collected from a variety of sources, embrace a vast range of topics dealing with the studying of Arabic manuscripts.
Keywords: Manuscripts, Arabic -- History -- Bibliography.; Codicology -- Dictionaries.; Arabic language -- Dictionaries -- English.; Paleography, Arabic -- Bibliography.; Arabic language -- Dictionaries.; Manuscrits arabes -- Histoire -- Bibliographie.; Codicologie -- Dictionnaires.; Arabe (Langue) -- Dictionnaires anglais.; Paléographie arabe -- Bibliographie.; REFERENCE.; Arabic language; Codicology; Manuscripts, Arabic; Paleography, Arabic; Arabische handschriften.; Terminologie.; Biblioteksvæsen, informations- og kommunikationsvidenskab -- Bog-, tidsskrift- og artikelfortegnelser.; Bibliographies; Dictionaries; History